2021
DOI: 10.1128/mra.00279-21
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of Veillonella nakazawae JCM 33966 T (=CCUG 74597 T ), Isolated from the Oral Cavity of Japanese Children

Abstract: We report the complete genome sequence of Veillonella nakazawae JCM 33966T (=CCUG 74597T). This bacterium is a member of the oral Veillonella and has the potential to be anticariogenic as an oral probiotic seed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The genomic features of all eight oral Veillonella species used in this study are shown in Table 1 . Additionally, detailed descriptions of the complete or draft genomes of six of the eight Veillonella oral species were previously reported [ 38 , 47 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…The genomic features of all eight oral Veillonella species used in this study are shown in Table 1 . Additionally, detailed descriptions of the complete or draft genomes of six of the eight Veillonella oral species were previously reported [ 38 , 47 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Veillonellae are strictly anaerobic Gram-negative cocci. The genus Veillonella consists of 16 characterized species [28][29][30][31][32][33][34], eight of which are routinely isolated from the oral cavity [33,35,36]. A unique characteristic of the genus is their lack of glucokinase and fructokinase that renders them unable to metabolize glucose, fructose and disaccharides.…”
Section: General Characteristicsmentioning
confidence: 99%
“…Among all genes, 73.6% were functionally annotated, and the rest were labeled as hypothetical proteins. More recently, as a result of the mounting interest attracted in oral veillonellae, several other draft and complete genomes were further deposited, these include V. atypica OK5, V. tobetsuensis ATCC BAA-2400T, V. parvula HSIVP1, V. nakazawae JCM33966 T [36,[53][54][55].…”
Section: Genomics and Geneticsmentioning
confidence: 99%